Keterkaitan Perencanaan Karier Siswa Dengan Konsep Diri Siswa Kelas XI Di SMKN 59 Jakarta - Ahiruddin Ahiruddin; Harun Rasjid; Agus Sakti Alim (Duconomics Sci-meet (Education & Economics Science Meet), 2021)
This study aims to determine the relationship between student career planning and self-concept of class XI student at SMKN 59 Jakarta. This study uses a descriptive method with a qualitative approach and purposive sampling technique, namely the technique of determining the sample with certain considerations. This technique can be interpreted as a sampling process by determining in advance the number of samples to be taken, the sample selection is carried out based on certain objectives, as long as it does not deviate from the characteristics of the specified sample. The research instrument used questionnaires, interviews, and observation distributed to 35 student in class XI Multimedia-1, guidance and counseling teachers and school principals. The result showed  a fairly good category, the relationship between student career planning and self-concept of class XI student at SMKN 59 Jakarta